(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2023)
This article will consider the effects of electromagnetic radiation at the molecular and cellular levels. The very possibility of biological effects of electromagnetic radiation with a frequency of 1011 and below is determined by the fact whether there is a primary reception of electromagnetic waves, that is, whether there is any physical mechanism for the interaction of biological structures with an electromagnetic field of non-thermal intensity, leading to a change in the functional activity of these structures. In this regard, it is important to understand what can happen in such an interaction at the microscopic level.